Dampak Kepemimpinan Transformasional Terhadap Pengembangan Karier dan Motivasi Kerja Pegawai di Kelurahan Tembong - Arif Rahman, Muhammad (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
This study aims to determine how much impact the workload has on job satisfaction. Quantitative causality is used as research design. Respondents were 188 nurses at the Bakti Timah Pangkalpinang Hospital. PLS SEM is used as a data analysis method. The results of the study found that workload had a significant negative impact on job satisfaction. Hospital management can increase nurse job satisfaction by reducing work demands through support provided by colleagues and superiors, fairness in dividing workloads, and more flexible working time. This research contributes to efforts to increase job satisfaction through workload on nurses.